Strategi Digital Marketing Kafe Dom Social Hub Dalam Meningkatkan Brand Awareness di Sosial Media Instagram Studi Deskriptif Kualitatif Pada Akun @Domsocialhub - Fithal Amin; Mochammad Mirza; Ari Suseno; Alamsyah Alamsyah (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Abstract. The increase in the number of Coffee Shops has created intense competition between them, especially along with the development of technology and the application of digital marketing. The importance of digital marketing, especially through social media, is the main focus in efforts to increase brand awareness of a product or service. In this context, digital marketing, especially through social media marketing, is described as an effective tool for achieving marketing goals by creating customer contacts, generating interest, and increasing purchase intentions. Analysis of brand awareness stages, from unconscious brands to top of mind, is an important part of understanding the process of forming a brand's image. Focus is also given to Instagram's role as an effective platform in enhancing brand identity, with an explanation of Instagram's popularity in promoting products and services. In this context, research focuses on the digital marketing communication strategy used by Dom Social Hub, a Coffee Shop in Tangerang City. The research aims to explore the advantages, disadvantages and obstacles that arise during the implementation of this strategy, with a focus on increasing brand awareness on social media platforms, especially Instagram. The object of this research explains the digital marketing strategy of the Dom Social Hub cafe in increasing brand awareness on Instagram social media. This research uses the constructivism paradigm. This research approach uses a qualitative descriptive approach.